2022
DOI: 10.3390/e24050681
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Fault Diagnosis of Rotating Machinery

Abstract: When rotating machinery fails, the consequent vibration signal contains rich fault feature information. However, the vibration signal bears the characteristics of nonlinearity and nonstationarity, and is easily disturbed by noise, thus it may be difficult to accurately extract hidden fault features. To extract effective fault features from the collected vibration signals and improve the diagnostic accuracy of weak faults, a novel method for fault diagnosis of rotating machinery is proposed. The new method is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Therefore, it holds great potential for application in the filed of diagnosing faults in rotating machinery. For example, Tang et al [78] utilized GA to determine the optimal embedding dimension and class number for composite dispersion entropy, as well as to optimize relevant parameters, resulting in significantly improved fault diagnosis efficiency. Tang et al [79] proposed a fault diagnosis method for double DBN bearings based on QGA and utilized quantum genetic algorithm (QGA) to optimize the parameters of Bi-DBN.…”
Section: Population-based Heuristicsmentioning
confidence: 99%
“…Therefore, it holds great potential for application in the filed of diagnosing faults in rotating machinery. For example, Tang et al [78] utilized GA to determine the optimal embedding dimension and class number for composite dispersion entropy, as well as to optimize relevant parameters, resulting in significantly improved fault diagnosis efficiency. Tang et al [79] proposed a fault diagnosis method for double DBN bearings based on QGA and utilized quantum genetic algorithm (QGA) to optimize the parameters of Bi-DBN.…”
Section: Population-based Heuristicsmentioning
confidence: 99%
“…It requires regular monitoring of all system components, including electrical machines. Electrical machines operating increasingly under severe conditions or at the limits of their capacity are subject to faults that can lead to failures [ 1 , 2 , 3 ]. Investigations in several industrial fields have revealed that rolling bearing elements (RBEs) are the main sources of failures for almost to of low- to high-power machines [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%